2021
DOI: 10.1155/2021/6680764
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐Analysis of Correlations between Altmetric Attention Score and Citations in Health Sciences

Abstract: Introduction. In recent years, several controversial reports of the correlation between altmetric score and citations have been published (range: -0.2 to 0.8). We conducted a meta-analysis to provide an in-depth statistical analysis of the correlation between altmetric score and number of citations in the field of health sciences. Methods. Three online databases (Web of Science, Scopus, and PubMed) were systematically searched, without language restrictions, from the earliest publication date available through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 41 publications
4
15
0
Order By: Relevance
“…Citation rate has been shown to have no correlation to AAS, 123 supported in our study by the incongruence in the article topics and types that constitute to the most impactful articles as determined by AAS or citation rate. Compared with previous studies that examined the most impactful ACL articles by citation density, 18 , 124 the results of the present study demonstrate a predominance of clinically focused studies and a relatively lower degree of interest in laboratory studies.…”
Section: Discussionsupporting
confidence: 71%
“…Citation rate has been shown to have no correlation to AAS, 123 supported in our study by the incongruence in the article topics and types that constitute to the most impactful articles as determined by AAS or citation rate. Compared with previous studies that examined the most impactful ACL articles by citation density, 18 , 124 the results of the present study demonstrate a predominance of clinically focused studies and a relatively lower degree of interest in laboratory studies.…”
Section: Discussionsupporting
confidence: 71%
“…To our knowledge, this is the first analysis to investigate the relationship between altmetric influence and subsequent academic citation using a modern, adjusted citation impact factor rather than raw citation count. In our sample of clinical and translational research, we found a stronger correlation between the AAS and citations than did a recent meta‐analysis examining this relationship across many fields 8 . This suggests that research focused on translation, which specifically aims to advance discoveries from the bench to the bedside, may benefit more from dissemination through public and community attention.…”
Section: Discussionmentioning
confidence: 41%
“…In our sample of clinical and translational research, we found a stronger correlation between the AAS and citations than did a recent meta‐analysis examining this relationship across many fields. 8 This suggests that research focused on translation, which specifically aims to advance discoveries from the bench to the bedside, may benefit more from dissemination through public and community attention. Further, we found that the AAS was more strongly related to the RCR than to total citations in this dataset.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations